Cycle time reduction of key products in capsule format of a local pharmaceutical company - Palmaria, Luz S.; Cruz, Edison (Quezon City University of the Philippines Diliman, Technology Management Center, 2010)
"The company can't meet delivery dates, no matter how much it tinkers with lead times." "Operators always have a backlog, regardless of the production schedule." Imagine the above scenarios in today's competitive environment. Delivering fast has become a challenge for most manufacturing companies. Long order-to-delivery time often results to late deliveries, unhappy customers, and lost sales. One strategic objective of most companies now is to improve its supply chain responsiveness : to deliver on-time and in-full. Thus, cycle time reduction has become the solution to this long order-to-delivery situation. Cycle Time Reduction or CTR consists of speeding up a company's order-to-delivery time to get product into the customer's hands as quickly as possible, at the lowest possible cost. It's a way of looking critically at a company's business processes-from order entry to scheduling to inventory management and shipping-to find opportunities to squeeze more efficiency out of them. This paper describes a CTR initiative done on some key products in capsule format by a local pharmaceutical company. This initiative led to the reduction of non-value adding activities which meant faster delivery and higher order fulfillment. This CTR project focused on the reduction of the cycle time in the conversion process of capsules by about 50 percent. The production processes were mapped, cycle times were determined and value-adding and non-value adding activities were pinpointed. This project aimed at eliminating waiting times and queue times and other contributing factors to long cycle time with the objective of improving on supply chain responsiveness and flexibility. DMAIC was used as theoretical framework in the study and techniques such as process mapping and value stream mapping were used to develop "maps" of the process flows to make activities more visible. These "maps" helped identify activities that are value adding or non-value adding, and also material flows, usages and losses.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Pharmaceutical industry